Linking strategic innovation management to operational success in the upstream petroleum regulatory commission of the South-South region - Emefo, Elechukwu; Ugwu, Kelechi; Asiabaka, Ihuoma Pauline; Ogolo, John Ibiwangi (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study focuses on strategic innovation management and operational performance using the Upstream Petroleum Regulatory Commission South-South Nigeria. The study adopted a survey design and questionnaire as instruments for data collection. The total population of the study comprised 497 staff of the organization. A calculation of the sample size using the Taro Yamane method produced a result of 222. A proportionate allocation formula was applied in the distribution of the survey in the following states: River State, Bayelsa, Akwa Ibom, Delta, and Edo State, Nigeria. Out of 222 copies of a questionnaire sent to the participants; only 207 were returned and utilized for the study while the remaining 15 copies were not used. The hypotheses were statistically tested and analyzed using ordinary least squares and Pearson correlation methods at a 5% level of significance. The findings of research objective one indicate that integrated management practices (IMP) have a significant impact on organizational effectiveness OE) when the p-value (.000) is less than a 5 % level of significance (p < 0.05). Finally, organizations should develop comprehensive innovation strategies that align with their overall business objectives. This involves integrating innovation across all functions and ensuring that it supports both short-term goals and long-term vision.